A note on the relationship between duration of mating season and flock fertility in some Ethiopian breeds of sheep and goats - Galal, E.S.E.; Awgichew, K. (1981)
Analyzes mating/parturition records on Ethiopian sheep and goat breeds, to study the effect of the duration of mating season on flock fertility, with emphasis on data related to cumulative percentage of females conceiving at different intervals of the mating season.